PELATIHAN PERPAJAKAN BREVET A&B BAGI ATLET (STUDI PADA ATLET GANTOLE PARALAYANG INDONESIA (PEPI) KABUPATEN BANDUNG BARAT) - Rachman, Fatwa Rubiar; Terawati, Mira Teram; Djuharoh, Aan Siti (Publika Citra Media, 2024)
Sportmen or athletes who receive or obtain income in connection with their participation in a competition or championship activity are obliged to carry out their tax obligations. Because athletes are included as individual tax subjects who receive income with deductions from Income Tax Article 21 and/or Article 26. Therefore, knowledge and technical skills are needed to carry out tax obligations properly and correctly. This activity was carried out as an embodiment of the Bandung Accounting Academy (A2B) in carrying out community service in accordance with the study program, namely tax accounting. The activity was entitled Tax Provision and Tax Training for Indonesian Paragliding athletes in West Bandung Regency. Organizing training, covering topics related to the field of taxation, as well as increasing the professional capabilities and competencies of HR in the scope of tax accounting for activity participants. Technically, this activity went according to target; all participants underwent the implementation process until completion, were declared to have passed, and were given a brevet A&B competency certificate.